Physicochemical properties of mango (Amropali cultivar) powder and its reconstituted product as affected by drying methods. Issue 1 (1st January 2020) - Akther, Shireen; Sultana, Afroza; Badsha, Md. Rahim; Rahman, Md. Mokhlesur; Alim, Md. Abdul; Amin, Amiza Mat
ABSTRACT: This study aimed to determine the effects of different drying methods on the physicochemical properties of mango powders (Amropali cultivar) and its reconstituted products. Six types of drying methods were employed, which were spray drying (SD), cabinet drying (CD), vacuum drying (VD), tunnel drying (TD), rotary oven drying (RoD) and gas oven drying (GoD). For drying temperature was maintained around 60 to 70°C for all dryers except for SD for which temperature was kept at 150°C. It was found that drying methods affected the physicochemical properties of mango powders (Amropali cultivar) and its reconstituted products. SD and CD powders showed better physicochemical properties (water activity, rehydration, solubility, and porosity) than other mango powder samples. In addition, mango powder produced through SD and CD methods showed lighter color, whereas mango powder prepared using other drying methods showed yellowish, dull, and dark colors. However, reconstituted products of SD and CD powders gave almost similar physicochemical properties compared to other dried samples. The present study concludes that SD powder and CD powder are more preferable in terms of producing high-quality products compared to other drying techniques.